STRATEGI PEMBELAJARAN TAHFIDZ AL-QURAN DI PONDOK PESANTREN DARUL ‘ILMI BANJARBARU - Muhammad Muhammad; Saifuddin Saifuddin (STAI AL FALAH Banjarbaru, 2020)
This research aims to find out how the strategy of learning tahfidz Al-Quran in Pondok Pesantren Darul 'Ilmi Banjarbaru as well as what factors affect it. This type of research is field research with a qualitative approach. The subject in this study is ustadz who built the tahfidz program at Pondok Pesantren Darul 'Ilmi. While the object in this study is the strategy of learning tahfidz Al-Quran in Pondok Pesantren Darul 'Ilmi Banjarbaru as well as the factors that influence it. Data mining is carried out through interview techniques, observation, and document analysis. Based on the results of the study, it is known that the learning strategy carried out by Ustadz in fostering the tahfidz program is an inquiry learning strategy and the selection of the strategy is appropriate and effective. The effectiveness is in accordance with the indicators that have been implemented by ustadz, among them at the screening stage of students who want to participate in the tahfidz program is a santri that has been completely tahsin in his reading. And the factors that influence the learning strategy of tahfidz Al-Quran in Pondok Pesantren Darul 'Ilmi Banjarbaru are ustadz, santri, allocation of time, and environment. Keywords: Learning strategies, Tahfidz Al-Quran, Pesantren.